2012
DOI: 10.1159/000336356
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Sensitivity of Parkinsonian Disorder Diagnoses in Two Swedish National Health Registers

Abstract: Background: Swedish population-based national health registers are widely used data sources in epidemiological research. Register-based diagnoses of Parkinson’s disease have not been validated against clinical information. Methods: Parkinson’s disease (PD) and other parkinsonian disorder diagnoses were ascertained in two registers, i.e. the National Patient Register (NPR) and the Cause of Death Register (CDR). Diagnoses were validated in terms of accuracy (positive predictive value) and sensitivity against dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(124 citation statements)
references
References 39 publications
4
120
0
Order By: Relevance
“…Second, we obtained PD diagnoses from the National Patient Register in which inpatient PD diagnoses have been validated against clinical diagnoses showing good accuracy; however, misclassification between PD and other parkinsonian disorders occurs. [23] We have no reason to believe that the magnitude of this misclassification differs by SES, therefore resulting in a bias toward the null. Another potential limitation in our study is surveillance bias; [36] participants in higher socioeconomic groups may be more health-conscious, more likely to seek care, resulting in earlier detection of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we obtained PD diagnoses from the National Patient Register in which inpatient PD diagnoses have been validated against clinical diagnoses showing good accuracy; however, misclassification between PD and other parkinsonian disorders occurs. [23] We have no reason to believe that the magnitude of this misclassification differs by SES, therefore resulting in a bias toward the null. Another potential limitation in our study is surveillance bias; [36] participants in higher socioeconomic groups may be more health-conscious, more likely to seek care, resulting in earlier detection of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous validation of hospital discharge diagnosis of PD against clinical diagnosis showed a positive predictive value of 70.8% and a sensitivity of 72.7%. [23] …”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of the PD diagnoses in the Swedish National Inpatient Register has been reported to be 70.8% [9]. The cases were identified by the main and up to seven contributory diagnoses.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, if occupational stress or other aspects related to occupation are associated with propensity to seek medical care, this could have differentially biased our results. To increase the accuracy of PD diagnoses, we only included hospital admissions and outpatient visits with PD as the main diagnosis, as suggested by a previous validation study …”
Section: Discussionmentioning
confidence: 99%
“…Date of ascertainment was defined as the first date of any PD diagnosis in the NPR or date of death in the CDR for those cases only identified at death. A previous validation study concluded that the NPR and CDR are valid data sources in epidemiological studies of PD with generally good accuracy and sensitivity …”
Section: Methodsmentioning
confidence: 99%